Recent Advances in Activated Carbon: Synthesis, Properties and Applications - Min H.S.; Kusuma H.S.; Sharma Y.C. (My University, 2025)
The world’s activated carbon market volume has increased rapidly in recent years due to environmental regulations. It is being used in a variety of fields including water treatment, air purification, and food processing. This volume in the Green Chemical Innovations and Sustainability Series studies the physical, biological, and chemical modification of activated carbon to enhance the adsorption performance. Recent experimental results indicating improved adsorption capacity are presented as well as novel applications using activated carbon. The authors focus on identifying potential precursors from agricultural waste, municipal waste, and industrial waste and investigate toxic pollutants. Features Demonstrates how researchers can produce synthetic adsorbents (activated carbon) via agricultural waste, industrial waste, and household waste. Describes the actions of adsorption capacity or percentage removal with respect to factors affecting the adsorption process. Investigates activated carbon's removal efficiency of dyes, organic compounds, pharmaceutically active compounds, heavy metals, pesticides, fungicides, herbicides, antibiotics, and other toxic pollutants Discusses the search for low-cost adsorbents that can be produced by using agricultural wastes, industrial wastes, and natural materials. © 2025 selection and editorial matter Ho Soon Min, Heri Septya Kusuma, and Yogesh Chandra Sharma; individual chapters, the contributors.